Effects of gamma radiation on engineered tomato biofortified for space agriculture by morphometry and fluorescence-based indices - Pagliarello, Riccardo; Bennici, Elisabetta; Di Sarcina, Ilaria; Villani, Maria Elena; Desiderio, Angiola; Nardi, Luca; Benvenuto, Eugenio; Cemmi, Alessia; Massa, Silvia (Frontiers in Plant Science, 2023)
Introduction: Future long-term space missions will focus to the solar system exploration, with the Moon and Mars as leading goals. Plant cultivation will provide fresh food as a healthy supplement to astronauts’ diet in confined and unhealthy outposts. Ionizing radiation (IR) are a main hazard in outer space for their capacity to generate oxidative stress and DNA damage. IR is a crucial issue not only for human survival, but also for plant development and related value-added fresh food harvest. To this end, efforts to figure out how biofortification of plants with antioxidant metabolites (such as anthocyanins) may contribute to improve their performances in space outposts are needed. Methods: MicroTom plants genetically engineered to express the Petunia hybrida PhAN4 gene, restoring the biosynthesis of anthocyanins in tomato, were used. Seeds and plants from wild type and engineered lines AN4-M and AN4-P2 were exposed to IR doses that they may experience during a long-term space mission, simulated through the administration of gamma radiation. Plant response was continuously evaluated along life cycle by a non-disturbing/non-destructive monitoring of biometric and multiparametric fluorescence-based indices at both phenotypic and phenological levels, and indirectly measuring changes occurring at the primary and secondary metabolism level. Results: Responses to gamma radiation were influenced by the phenological stage, dose and genotype. Wild type and engineered plants did not complete a seed-to-seed cycle under the exceptional condition of 30 Gy absorbed dose, but were able to cope with 0.5 and 5 Gy producing fruits and vital seeds. In particular, the AN4-M seeds and plants showed advantages over wild type: negligible variation of fluorimetric parameters related to primary metabolism, no alteration or improvement of yield traits at maturity while maintaining smaller habitus than wild type, biosynthesis of anthocyanins and maintained levels of these compounds compared to non-irradiated controls of the same age. Discussion: These findings may be useful in understanding phenotypic effects of IR on plant growth in space, and lead to the exploitation of new breeding efforts to optimize plant performances to develop appropriate ideotypes for future long-term space exploration extending the potential of plants to serve as high-value product source.